P-D15 Peripheral blood lymphocyte HIV DNA levels correlate with HIV associated neurocognitive disorders. (January 2016) - Jumare, Jibreel; Sunshine, Sara; Li, Jonathan; Ahmed, Hayat; Burdo, Tricia; Eyzaguirre, Lindsay; Umllauf, Anya; Cherner, Mariana; Abimiku, Alash'le; Charurat, Man; Royal, Walter; Blattner, William
Abstract : Introduction: Mononuclear cells play a key role in facilitating the pathogenic mechanisms leading to HIV associated neurocognitive disorders (HAND). We examined the association between levels of HIV DNA within monocytes and lymphocytes and HAND. Method: Blood samples were obtained from 40 antiretroviral naive participants in Nigeria. CD14+ cells and T&B lymphocytes were isolated from peripheral blood mononuclear cells by bead separation (84-98% purity for CD14+ cells). Total HIV DNA was quantified using real-time PCR assay targeting HIV LTR-gag and cell input numbers determined by the number of CCR5 copies/sample. Utilizing a 7-domain neuropsychological test battery and activities of daily living assessment, participants were classified as either unimpaired, having asymptomatic neurocognitive impairment (ANI), minor neurocognitive disorder (MND), or HIV associated dementia (HAD) in line with the Frascati criteria. Results: The mean log10 HIV DNA copies/106 cells were higher for T & B lymphocytes than for CD14+ monocytes ( P -value: 0.0002). In a multivariable linear regression adjusting for CD4 count, viral load and lymphocyte count, compared to unimpaired individuals, the mean copy numbers for T & B lymphocytes were higher among those with HAND ( P -value: 0.01) and for those with MND [ P -value: 0.02 (Tukey adjusted: 0.07)]. In a multivariable logistic regression adjusting for same variables, the odds of cognitive impairment was 6.7 times greater per log increase in HIV DNA within T & B lymphocytes ( P -value: 0.02). There was no significant association between cognitive impairment and HIV DNA within CD14+ monocytes. Conclusions: In this cohort we found a strong association between levels of cell-associated HIV DNA within the lymphocyte subset and HAND. Further studies looking at similar association among patients with suppressed viremia are required for inference on integrated DNA.